Role of the Ste20 Like Kinase in Muscle Development and Muscular Dystrophy - Pryce, Benjamin (Université d'Ottawa / University of Ottawa, 2019)
Duchenne Muscular Dystrophy (DMD) is a fatal X-linked disorder affecting 1 out of every 3500 male births. The underlying cause of DMD is mutations within the dystrophin gene resulting in loss of protein expression, which leads to myofiber instability and damage. The constant damage of skeletal muscle causes sustained immune infiltration, marked by increased levels of cytokines, such as TGF-beta. Interestingly, TGF-beta can decrease the myogenic potential of satellite cells, thus preventing muscle regeneration. Previously, our lab has shown that knockdown of the Ste20 Like Kinase, SLK, in normal mammary epithelial cells was sufficient to delay TGF-beta induced epithelial to mesenchymal transition. Therefore, we speculated that decreasing SLK levels would be sufficient to decrease the anti-myogenic effects of TGF-beta both in cultured myoblasts and in a mouse model of muscular dystrophy. In the first section of this study, we explored the effect of muscle specific deletion of SLK on muscle development and regeneration. Skeletal muscle specific deletion of SLK did not impair muscle development, but caused a myopathy in older mice. Additionally, muscle regeneration was delayed, but not inhibited by SLK deletion. These findings indicated that SLK has beneficial roles in skeletal muscle, but was not absolutely required for optimal muscle development and regeneration. In the second section, we investigated the potential for SLK knockdown to mitigate the anti-myogenic effects of TGF-beta in vitro. Decreasing levels of SLK restored myoblast differentiation in the presence of TGF-beta in a p38 dependent manner. In the final section, we determined that SLK levels are elevated in dystrophic muscle and that subsequent deletion of SLK in the mdx mouse enhances terminal differentiation of myoblasts without further exacerbating the pathology of the disease. Collectively, this work demonstrates that SLK inhibition can provide a protective effect against the anti-myogenic effects of TGF-beta via upregulation of p38 activity.
Keywords: SLK; Skeletal Muscle; Muscular Dystrophy